Analysis and Design of Dashboard Information System Results of Nutrition Status Monitoring Year 2016 As a Supporter of Community Nutrition Policy - Wibowo, S; Kamso, S (KnE Life Sciences, 2019)
The availability of data and information presented comprehensively and easily understood is still very limited until it has not been able to fully support the process of decision making and the formulation of appropriate policies for the organization. A dashboards information system is an application that provides information about key indicators of organizational activity at a glance in a single screen. Dashboards can be a tool to present summaries of data and information in an easily understandable visual form. This study aimed to analyze and design the dashboard information system based on Nutrition Status Monitoring surveys conducted in 2016 by the Ministry of Health. Nutrition Status Monitoring is a survey that produces an overview of nutritional status and indicators of community nutrition program performance outcomes in 514 districts/cities in 34 provinces in Indonesia. The method used in this research was the development of a methodology for the construction of an information dashboard with a focus on the activity of requirement identification, planning, and design of the prototype. The output of this research was the design of the dashboard information system that processes and presents data/information on the results of Monitoring of Nutritional Status of 2016 in the form of easy-to-understand visualization. With this information system, it could be an effective means to measure the performance of the organization and support relevant stakeholders in the process of taking action intervention and policy formulation to improve the nutrition of the community. Keywords: dashboard, Nutrition Status Monitoring, information system, community nutrition